Effect of soil nutrient status on stress tolerance in Proteaceae - Manuel, Theodore Llewellyn (Department of Biological Sciences, 2017)
Protea lepidocarpodendron grown on low, medium and high nutrient treatments exhibited the lowest, and similar evapotanspiration rates respectively over a 9 day water stress cycle (experimental period). In stressed and unstressed treatments, stomatal conductance and transpiration rates of plants grown on the low nutrient treatment was generally lower than that of plants grown on the medium and high nutrient treatments where stomatal conductance and transpiration rates were similar. Stressed plants grown on the low, medium and high nutrient treatments exhibited the lowest, intermediate and highest photosynthetic rates respectively. Stessed plants grown on the medium and high nutrient treatments exhibited a dramatic decrease in transpiration rates ands stomatal conductance from day 5 to 7, and a dramatic decrease in photosynthetic rates from day 3 to 7. Stressed plants grown on the low nutrient treatment showed a far less dramatic decrease in transpiration rate, stomatal conductance and photosynthetic rate over the 9 day period. For stressed plants, photosynthetic rates varied between 0.08-5.39 uMOLm⁻²s⁻¹, 1.17-7.48uMOlm⁻²s⁻¹ and 1.15-8.65uMOLm⁻²s⁻¹ for plants grown on low, medium and high nutient treatments respectively. Unstressed plants grown on low. medium and high nutrient treatments exhibited the lowest, highest and intermediate photosynthetic rates respectively. In all stressed treatments, photosynthetic rates showed a steady decline from day 1 to day 7, whereafter a dramatic increase occurred in the medium and high nutrient treatments, and a less dramatic increase in plants grown on the low nutrient treatment. These decreases and increases in photosynthetic rates was not parallelled in the stomatal conductance and transpiration rates of the unstressed plants. For unstressed plants, photosynthetic rates varied between 1.4s-4.4 uMOLm⁻²-s⁻¹, 1.65-6.7 uMOLm⁻²s⁻¹ and 3.42-8.76 uMoLm⁻²s⁻¹ for plants grown on low, medium and high nutrient treatments respectively. Plants grown on low nutrient treatments exhibited the highest LSW (182.3 gm⁻²), highest whole plant mass (WPM) (1.07g), followed by high (LSW=1.76 gm⁻²,WPM=0.83g) and medium (LSW=167.28 gm⁻² ,WPM=0.79g) nutrient treatments. Total plant nitrogen content was inversely related to LSW and WPM on low (3.84 mgNplant⁻¹), high (4.18 mgNplant⁻¹) and medium (5.28 mgNplant⁻¹) treatments. Root : ratio between treatments were similar.